Обробка деталей шліфуванням за параметром шорсткості обробленої поверхні - Шахбазов, Я. О.; Ничкало, В. С. (Видавництво Державного університету "Львівська політехніка", 2000)
There are analysed grind process laws and technological parameters’ influence for surfaces research formation. Research of stages’ overlapping opportunities for preliminary and grinding process.